Navigating the Nexus: Exploring the Relationship between Intellectual Capital, Financial Performance, and Firm Value - Andi Surya (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
While previous study has drawn attention to the relationship between intellectual capital, financial performance, and firm value, there is still room for empirical research into the role of mediating factor between them. This research aims to determine the role of intellectual capital and financial performance in improving the firm value of the manufacturing companies listed on the Indonesia Stock Exchange. For this study, we collected financial reports from seven manufacturing companies over five years from 2017 to 2021. We employed a quantitative method, specifically path analysis using linear regression analysis, to test our hypotheses. The results demonstrate that there is no effect of intellectual capital on both financial performance and firm value, and no mediating effect exists either. However, the effect of company performance on firm value was established in the study. The research results create a chasm, suggesting three variables to think about when making investment decisions.